Sulfamethazine removal by means of a combined process coupling an oxidation pretreatment and activated sludge culture – preliminary results. Issue 21 (2nd November 2017) - Saidi, Imen; Fourcade, Florence; Floner, Didier; Soutrel, Isabelle; Bellakhal, Nizar; Amrane, Abdeltif; Geneste, Florence
ABSTRACT: A coupled electrochemical process and biological treatment was used to remove a biorecalcitrant antibiotic: sulfamethazine (SMT). The pretreatment was performed in a home-made flow cell involving graphite felt as a working electrode at potentials of 1 and 1.6 V/saturated calomel electrode (SCE); it was followed by a biological process involving activated sludge purchased from a local wastewater treatment plant. Activated sludge cultures of pretreated and non-pretreated SMT solution were carried out for 3 weeks, and different parameters were monitored, especially total organic carbon (TOC) and SMT concentrations. high-performance liquid chromatography results revealed that the target molecule was not assimilated by activated sludge. However, and confirming the improvement previously observed for the biological oxygen demand/chemical oxygen demand (BOD5 /COD) ratio, from 0.08 before electrolysis to 0.58 after electrolysis, a pretreatment step in oxidation at 1.6 V/SCE led to a fast decrease of TOC during the subsequent biological treatment, since the mineralization yields increased from 10% for a non-pretreated SMT solution to 76.6% after electrolysis in oxidation (1.6 V/SCE), confirming the efficiency of coupling the electro-oxidation process with a biological treatment for the mineralization of SMT. Moreover, when the electrolysis was performed at 1 V/SCE, no biodegradation was observed, underlining the importance of the electrochemical pretreatment.